2011
DOI: 10.1039/c0cp01930e
|View full text |Cite
|
Sign up to set email alerts
|

Templated growth of platinum nanowheels using the inhomogeneous reaction environment of bicelles

Abstract: COVER ARTICLE Song, Shelnutt et al. Templated growth of platinum nanowheels using the inhomogeneous reaction environment of bicelles HOT ARTICLE Zhao et al. Di-lanthanide encapsulated into large fullerene C 100 : a DFT survey 4846

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
(46 reference statements)
1
29
0
Order By: Relevance
“…80,81 Today, the term “bicelle” has become so popular that it was even applied to flat, disk-like aggregates formed by linear peptide copolymers with different length hydrophobic and hydrophilic portions. 82 The potential pharmaceutical application of bicellar formulations to the skin has been investigated in detail and has been reviewed.…”
Section: What Are Bicelles?mentioning
confidence: 99%
“…80,81 Today, the term “bicelle” has become so popular that it was even applied to flat, disk-like aggregates formed by linear peptide copolymers with different length hydrophobic and hydrophilic portions. 82 The potential pharmaceutical application of bicellar formulations to the skin has been investigated in detail and has been reviewed.…”
Section: What Are Bicelles?mentioning
confidence: 99%
“…In the field of nanotechnology, bicelles were used as a temporary scaffold to synthesize rigid organic nanodisks by polymerization [312] and to generate platinum nanowheels [313,314]. Bicelles were used to build assemblies of multiple highly fluid free lipid bilayers that are tethered together by cholesterol-anchored double-stranded DNA [315].…”
Section: New and Notablementioning
confidence: 99%
“…Bicelles, which possess both low- and high- curvature regions within a bilayer disks, represent a class of model membranes used in nuclear magnetic resonance (NMR) structural studies of membrane biomolecules [41] , [54] , [55] , [56] , but they have found additional applications in biomedical sciences [57] , [58] , [59] . The bicellar templates were utilized previously to control the growth of platinum with ascorbic acid as a reducer, producing metal nanodisks and nanowheels [60] , [61] . Other phospholipid structures, like spherical liposomes, were also used for gold deposition to assemble biodegradable plasmon resonant nanoshells, which were used for the laser-induced release of molecules encapsulated into these liposomes [62] , [63] , [64] .…”
Section: Discussionmentioning
confidence: 99%